USING THE NEW FORMS OF LABOUR ORGANIZATION TO INCREASE EMPLOYMENT IN UKRAINE - Kravchenko, Olena (Journal of European Economy, 2007)
In this article, the author analyses a complex of questions related to changes in the forms of labour organization preconditioned by the large-scale implementation of information and communication technologies. The author determines major tendencies in telework development and defines the most relevant problems in this sphere. Underscoring the importance of tele-employment at the labour markets of foreign countries, the author reviews the possibilities of their usage in Ukraine and analyses the consequences of using distant work giving consideration for their influence on different spheres of the country’s economic activity.